2022
DOI: 10.1055/s-0042-1757881
|View full text |Cite
|
Sign up to set email alerts
|

Sibling Screening in Pediatric Brucellosis

Abstract: Objective Routine screening of household members of index cases is a priority in regions where brucellosis is endemic. This study aimed to identify seropositive and seronegative pediatric patients by screening the siblings of our pediatric patients diagnosed with brucellosis (index cases) and to investigate the relationships among these groups by comparatively evaluating their demographic, epidemiological, clinical, and laboratory characteristics. Materials and Methods Eighty-five pediatric household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…However, these complications are generally mild and can be resolved quickly with antimicrobial therapy. [5] In rare cases, thrombocytopenia can be severe and lead to skin and mucous membrane bleeding. Studies on hematologic findings have reported varying rates of leukopenia, thrombocytopenia and pancytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…However, these complications are generally mild and can be resolved quickly with antimicrobial therapy. [5] In rare cases, thrombocytopenia can be severe and lead to skin and mucous membrane bleeding. Studies on hematologic findings have reported varying rates of leukopenia, thrombocytopenia and pancytopenia.…”
Section: Discussionmentioning
confidence: 99%